The Cross, African(ness), and Identity in Mark's Passion Narrative - Hombana, Mphumezi (Scriptura, 2023)
In this article, the Markan Passion Narrative has been juxtaposed with Africanness, shedding light on vital aspects of Jesus' identity and the significance of his sacrifice within an African context. While existing scholarship has explored African characters in the New Testament, little attention has been paid to how the Markan Passion Narrative engages with African(ness), especially concerning Jesus' crucifixion, death, and resurrection. This article aims to delve into this relationship by conducting a literary analysis of symbols, themes, and narrative techniques employed in the Passion Narrative, considering the historical and cultural backdrop of its composition. The study seeks to uncover how these elements resonate with Mark's account and African(ness), contributing to discussions on social identity and ethical issues confronting contemporary African societies.